Cardiovascular Risk Factors in Pre-dialysis Chronic Kidney Disease patients of Nepal - Dahal, Kashyap; Baral, A.; Sah, K.K.; Shrestha, J.R.; Niraula, A.; Hada, R. (Journal of Advances in Internal Medicine, 2020)
Background and Aims: Cardiovascular disease (CVD) is the commonest cause of morbidity and mortality in patients with chronic kidney disease (CKD) due to increased prevalence of traditional and nontraditional CVD risk factors. Our study aimed to evaluate these risk factors in pre-dialysis Nepalese CKD patients.Methods: This was a cross-sectional study conducted in Department of Nephrology, Bir hospital. Total 100 consecutive pre-dialysis CKD patients were enrolled. Ten traditional and six nontraditional CVD risk factors were analyzed and compared between CKD stages. Descriptive statistics was used to illustrate the socio-demographic and clinical characteristics, chi square test for categorical variables and multiple logistic regression analysis was done to determine the risk factors of CVD in CKD patients. p-value